2007
DOI: 10.1111/j.1442-2042.2007.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Success of sildenafil treatment in neurogenic female sexual dysfunction caused by L5‐S1 intervertebral disk rupture: A case report

Abstract: Female sexual dysfunction can be founded by disorders of sexual desire, arousal, orgasm, and sexual pain. Physiologic sexual dysfunction can, in many cases, be the result of impaired neurovascular tone to the clitoris and vagina. The vagina and clitoris both contain erectile tissue and phosphodiesterase type 5 (PDE5). Accordingly, the use of sildenafil, a PDE5 inhibitor, has been studied in relation to neurogenic female sexual dysfunction. The present case report addresses neurogenic female sexual dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Although the treatment of FSAD has various options including hormone therapy, phosphodiesterase (PDE) inhibitors and alphablockers, mostly through enhancement of the vaginal blood flow [6,[8][9][10][11][12][13], they possess undesired side effects following their systemic administration. For examples, since PDE inhibitors and ablockers affected the systemic blood pressure and cardiac function, their clinical usages often resulted in adverse activities in cardiovascular regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the treatment of FSAD has various options including hormone therapy, phosphodiesterase (PDE) inhibitors and alphablockers, mostly through enhancement of the vaginal blood flow [6,[8][9][10][11][12][13], they possess undesired side effects following their systemic administration. For examples, since PDE inhibitors and ablockers affected the systemic blood pressure and cardiac function, their clinical usages often resulted in adverse activities in cardiovascular regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The data were gathered using the FSFI questionnaire, and showed that the females' sexual function score increased from 48 to 57. Thus, the findings of that study showed that sildenafil citrate increased the subjects' sexual stimulation and lubrication (p < 0.001) [21].…”
Section: Resultsmentioning
confidence: 68%
“…Ferrara and Zaslau (2007) used sildenafil citrate in order to treat sexual dysfunction in women suffering from neurogenic injury (L5-S1 disk herniation). The data were gathered using the FSFI questionnaire, and showed that the females' sexual function score increased from 48 to 57.…”
Section: Resultsmentioning
confidence: 99%
“…Another case about sildenafil treatment in neurogenic female sexual dysfunction caused by L5-S1 intervertebral disk rupture in 2007. [ 16 ] We present here addional four cases. Interesting point of our cases is that all disc occurred at the level L5-S1.…”
Section: Discussionmentioning
confidence: 99%